The artistic concept of "childhood" in the story "Dandelion wine" by R. Bradbury (Literatures of the World: Poetics, Mentality and Spirituality, 2014)
The article contains ananalysis ok the realization peculiarity in Ray Bradbury’s novel "Dandelion Wine" ok artistic concept "childhood" as the embodiment of autor hideological priorities that form the individual author's view of the world and the sys-tem of ethical-aesthetic dominant in the studied story.
Keywords: artistic concept; mental formation; fantasy; psychologism; lyric-epic; prose